Identification and combinatorial engineering of indole-3-acetic acid synthetic pathways in Paenibacillus polymyxa - Huimin Sun; Jikun Zhang; Wenteng Liu; Wenhui E; Xin Wang; Hui Li; Yanru Cui; Dongying Zhao; Kai Liu; Binghai Du; Yanqin Ding; Chengqiang Wang (Biotechnology for Biofuels and Bioproducts, 2022)
Highlights 1. Verifying an entire native IPyA pathway of IAA synthesis in P. polymyxa. 2. Introducing heterologous IAM and IPyA pathways of IAA synthesis to P. polymyxa. 3. Selecting and analyzing a novel strong promoter P 04420 to express IAA synthesis genes.